Improving the Compliance of Electronic Inpatient Daily Census Filling (Seharie) at RSUD Dr. Iskak Tulungagung: Peningkatan Kesesuaian Pengisian Sensus Harian Rawat Inap Elektronik (Seharie) Di RSUD Dr. Iskak Tulungagung - Pertiwi, Firda Latifani; Lailadewi, Fiqda Tridiningrat (Procedia of Engineering and Life Science, 2025)
RSUD dr. Iskak has implemented an electronic medical record so that the recording of the daily inpatient census can be done electronically. Based on data for July 2023 and October 2023 based on 29 categories of inpatient daily census, 84% (16 categories) are suitable, and 16% (3 categories) are not in accordance with the category of inpatient daily census. The inappropriate categories are how to enter for transfer patients, how to exit for deceased patients, and the doctor in charge of the patient. The inaccuracy of filling out the daily census has an effect on the quality of the information produced. This study is descriptive, as the population of the electronic inpatient daily census research for July 2023 -October 2023 is 153 entries. The sample used in this study was a saturated sampling of 153 census entries. Data collected through interviews and observations. The data was analyzed using the fishbon diagram method with a risk assessment approach. The results of the study show that the factors that cause the inconsistency of filling out the electronic daily inpatient census are. Prosedure (there has been no update of procedural operational standards with the latest system in 2022), Policy (lack of warnings related to inconsistencies in filling in census data), Environment (difficulties in filling out the census on time during holidays), Human (weak understanding of filling out the daily census for hospitalization, and not yet knowing the information generated based on census data input), Management (high admin burden), System (many less effective menu options). The hospital’s medical records are expected to be able to make changes to procedural operational standards with the latest conditions, coordinating with the information technology management installation section related to simplifying the filling of the inpatient daily census and the room admin for the accuracy of recording.